2022
DOI: 10.1021/acs.chemmater.2c00996
|View full text |Cite
|
Sign up to set email alerts
|

Tough Antibacterial Metallopolymer Double-Network Hydrogels via Dual Polymerization

Abstract: We report the preparation of tough double-network (DN) metallopolymer antibacterial hydrogels through dual polymerization. DN hydrogels are composed of the first network of cationic cobaltocenium polyelectrolytes enabled using ring-opening metathesis polymerization and the second network of polymers prepared using radical polymerization. These DN hydrogels exhibited a very high compressive stress (up to ∼120 MPa). The introduction of boronic acid and ionic conjugation with β-lactam antibiotics endowed the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…As shown in Scheme 1, cobaltocenium-containing polythioethers were synthesized by sequential photo-polymerization and post-polymerization modification via the CuAAC click reaction. Compared with the previous methods to prepare cobaltocenium-containing polyelectrolytes, 37–40 highly efficient post-polymerization modification of the precursor polymer can not only ensure the quantitative grafting of cobaltocenium to the polymeric framework, but also ensures the consistency of molecular weight information between the product and the polymer precursor, and therefore provides an alternative method to overcome the challenge on the molecular weight characterization of metallo-polyelectrolyte. 41…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Scheme 1, cobaltocenium-containing polythioethers were synthesized by sequential photo-polymerization and post-polymerization modification via the CuAAC click reaction. Compared with the previous methods to prepare cobaltocenium-containing polyelectrolytes, 37–40 highly efficient post-polymerization modification of the precursor polymer can not only ensure the quantitative grafting of cobaltocenium to the polymeric framework, but also ensures the consistency of molecular weight information between the product and the polymer precursor, and therefore provides an alternative method to overcome the challenge on the molecular weight characterization of metallo-polyelectrolyte. 41…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the previous methods to prepare cobaltocenium-containing polyelectrolytes, [37][38][39][40] highly efficient postpolymerization modification of the precursor polymer can not only ensure the quantitative grafting of cobaltocenium to the polymeric framework, but also ensures the consistency of molecular weight information between the product and the polymer precursor, and therefore provides an alternative method to overcome the challenge on the molecular weight characterization of metallo-polyelectrolyte. 41 The synthetic method of the target inhibitors is very straightforward and successful preparation can be identified using NMR and FT-IR.…”
Section: Polymer Chemistry Papermentioning
confidence: 99%
“…21,22 Recently, many kinds of antibacterial agents were introduced into the DN hydrogels with the purpose of integrating antibacterial property. [23][24][25] Hu et al developed a DN hydrogel where gradient silver nanoparticles were in situ formed on the hydrogel surface. 26 It was found that this hydrogel exhibited excellent antibacterial activity against both Gram-negative bacteria and Gram-positive bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Creating mechanically robust and tough hydrogels has flourished over the past two decades, which has enabled the practical application of hydrogels in various fields requiring load-bearing, such as scaffolds for tissue engineering, medical implants, wound dressings, , flexible and wearable devices, etc. The basic principle for developing tough hydrogels is incorporating built-in energy dissipation mechanisms through covalent/noncovalent bonds as sacrificial bonds. , Recently, incorporating dynamic noncovalent bonds into hydrogels as reversible sacrificial bonds has attracted extensive attention since the dynamic bonds endow hydrogels with not only high toughness but also self-healing ability. , Hydrogels with ionic bonds, such as polyampholyte hydrogels (PA gels), polyion-complex hydrogels (PIC gels), , and polyelectrolytes complexed with multivalent ionic groups, are a typical representative of hydrogels with dynamic noncovalent bonds. Among them, the PA gels consisting of polymer networks bearing randomly dispersed cationic and anionic repeat groups exhibit tunable multiple mechanical properties over wide ranges.…”
Section: Introductionmentioning
confidence: 99%